Visualização de Afinidades Entre Parlamentares Mediante Dados de Votações no Senado Brasileiro - Sant'Ana, Ricardo César Gonçalves [UNESP]; Rodrigues, Fernando de Assis [UNESP] (My University, 2013)
The expansion of citizen participation in the public sphere depends directly of access information on the performance of elected representatives, especially with regard to their voting decisions during their terms. The Information Science can assist in this process, proposing and evaluating models of access to such information that may be obtained from data to be provided by the official websites from legislative, in levels federal, state and municipal. It is proposed in this paper to analyze the process of collecting and using of data about votes of senators in order to promote the use of this model in other spheres. From analyzed data a affinity matrix was developed to identifying the relationship between each of the parliamentary with others, based on the similarities of the decisions taken in all the open votes. It was also analyzed the development of initial visualizations and the extension of the scope of the search through the application of data obtained in all the affinities between parliamentarians and to obtain an average affinity between parties, enabling new dimensions of analysis to the data collected. The preparation of the full matrix of relations of affinity among parliamentarians can provide a new horizon of possibilities for developing new forms of visualization and analysis, increasing the visibility of parliamentary actions with society.
Viewing by parliamentary affinities between data votes in the senate Brazilian
Keywords: Data Visualization; Open Data; Public Transparency